Amphiphysin IIm Is Required for Survival of Chlamydia pneumoniae in Macrophages - Gold, Elizabeth S. (The Rockefeller University Press, 2004)
Macrophages play a critical role in both innate and acquired immunity because of their unique ability to internalize, kill, and degrade bacterial pathogens through the process of phagocytosis. The adaptor protein, amphiphysin IIm, participates in phagocytosis and is transiently associated with early phagosomes. Certain pathogens, including Chlamydia pneumoniae, have evolved mechanisms to subvert macrophage phagosome maturation and, thus, are able to survive within these cells. We report here that, although amphiphysin IIm is usually only transiently associated with the phagosome, it is indefinitely retained on vacuoles containing C. pneumoniae. Under these wild-type conditions, C. pneumoniae do not elicit significant nitric oxide (NO) production and are not killed. Abrogation of amphiphysin IIm function results in C. pneumoniae–induced NO production and in the sterilization of the vacuole. The data suggest that C. pneumoniae retains amphiphysin IIm on the vacuole to survive within the macrophage.